Modelling of Non-Equilibrium Water Condensation in Natural Gas Flowing Through Joule-Thomson Valve - Che Jaafar, Nor Aini Aslah (IRC, 2016)
As raw natural gas exits from oil and gas reservoirs, it is normally saturated with liquid and/or water vapour. Conventionally, a few technologies are used to reduce the water content, including dehydration using throttling valve in which the Joule-Thomson effect is applied. However, most of the current literatures merely focused on hydrodynamics and equilibrium condensation, where the non-equilibrium condensation dynamics are not reported. Thus, this project aims to develop a model for non-equilibrium condensation phenomenon, to be able to provide a more accurate model to be applied in real industry. In this project, after the literature research is conducted, a model is developed, simulated and validated with experimental data. Sensitivity analysis is conducted as well, to observe how other variables such as feed gas composition and throat size affect the outlet temperature. In data gathering, the simulated outlet temperature for different inlet pressure is recorded.